Visual duration bisection in profoundly deaf individuals - Feng Zhang; Kaige Jin; Sainan Zhang (PeerJ, 2020)
Background Previous research has been designed to study the effect of hearing loss on supra-second duration estimation in the visual channel and position effect of visual abilities among deaf populations. The current study aimed to investigate the sub-second duration perception of different visual fields in profoundly deaf individuals. Methods A total of 16 profoundly deaf undergraduates and 16 hearing undergraduates completed a visual duration bisection task in which participants made judgments about whether a series of probe durations that were linearly spaced from 200 ms to 800 ms at 100 ms intervals were more similar to a standard short duration (200 ms) or a standard long duration (800 ms). The probe stimuli were presented in the center, left, or right of the screen. A repeated measure analysis of variance (ANOVA) with a between-participants factor of group and a within-participants factor of position, and a one-sample t-test were conducted. Results The Weber ratio (WR) values of deaf participants were significantly higher than those of hearing participants, regardless of the presented positions of the visual stimulus. The bisection point (BP) value of deaf participants was significantly lower than 500 ms (average mean of 200/800 ms) and the BP value of hearing participants did not significantly differ from 500 ms, although the overall difference of BP values between the deaf group and hearing group did not reach significance. For deaf participants, the BP value in the center condition was significantly lower than 500 ms; however, the difference between the BP value in the left condition and 500 ms did not reach significance, indicating that their duration discrimination accuracy in the left visual field was better than that in the center visual field. Conclusions Hearing loss impaired visual sub-second duration perception, and deaf individuals showed a left visual field advantage of duration discrimination accuracy during the visual duration bisection task.